Power and Media: The History and Formation of the Newspaper «Government Gazette» - Marina Evgenyevna Apon (Управленческое консультирование)
This article demonstrates the process of creating the first «common and exclusive to all min istries and chief departments» the official newspapers - «Government Gazette» in the second half of the XIX century. Focusing on political intrigue against the Minister of war D. A. Miliutin, the author notes that the need for the establishment of a unified government newspaper primarily dictated by the problem of the unity of state administration due to the absence in Russia of a United government with a homogeneous composition.